RICE IN COLONIAL AND POST COLONIAL SOUTHEAST ASIA: A FOOD REGIME ANALYSIS (History Department, Semarang State University and Historian Society of Indonesia, 2015)
This paper traces the ways in which rice, as a global commodity, has been produced and sold in various regions in Southeast Asia from the colonial era to the present days. This paper employs a food regime analysis first introduced by Harriet Friedmann (1982) and later developed together with Philip McMichael (1989) to look at the global political economy of rice. In this paper, it will be shown how various colonial and post colonial states in Southeast Asia (including Thailand who was never formally colonized) through their policies have practically divided the region where Burma (now Myanmar), Thailand and Vietnam in the mainland have become major rice producer and exporter, while Indonesia, Malaya (now Malaysia), and the Philippines in the archipelagic Southeast Asia have become major rice importers although at the same time producers and exporters of other agro-commodities (coffee, sugar, rubber).Keywords: rice history, food regime, Southeast Asia Artikel ini menelusuri cara di mana padi sebagai komoditas dunia diproduksi dan dijual di beberapa daerah di Asia Tenggara mulai zaman kolonial sampai sekarang. Artikel ini menggunakan analisis “food regime” yang pertama kali diperkenalkan oleh Harrier Friedman (1982) dan kemudian dikembangkan bersama oleh Philip (1989) untuk mengetahui politik ekonomi global dari padi. Dalam artikel ini, akan dilihat mengenai bagaimana negara kolonial dan pasca-kolonial yanb berbeda di Asia Tenggara (termasuk Thailand yang tidak pernah dijajah sebelumnya) melalui kebiakannya, yang hampir membagi wilayahnya, di mana Burma (Myanmar), Thailand, dan Vietnam telah menjadi produsen dan eksportir utama terbesar, sedangkan Indonesia dan Malaya (Malaysia) dan Filipina di Asia Tenggara telah menjadi produsen dan eksportir komoditas pertanian lain (kopi, gula, karet) dalam waktu yang bersamaan.Kata kunci: sejarah beras, food regime, Asia Tenggara.